Phasic disappearance of left circumflex coronary artery from an early complication of mitral valve surgery. Issue 11 (21st October 2015) - Devabhaktuni, Subodh; Sunkara, Nirmal; Ahsan, Chowdhury
Key Clinical Message: LV pseudoaneurysm can be a late complication of mitral valve replacement. In our case, it was an early postoperative complication. This pseudoaneurysm was causing compression of LCX artery during systole, leading to presentation of NSTEMI two weeks after the surgery. Abstract : LV pseudoaneurysm can be a late complication of mitral valve replacement. In our case, it was an early postoperative complication. This pseudoaneurysm was causing compression of LCX artery during systole, leading to presentation of NSTEMI two weeks after the surgery.